Adenosine pathway regulates inflammation during Plasmodium vivax infection - Diniz, Suelen Queiroz; Figueiredo, Maria Marta; Costa, Pedro Augusto Carvalho; Martins-Filho, Olindo Assis; Teixeira-Carvalho, Andrea; Pereira, Dhélio Batista; Shugiro Tada, Mauro; Crocco Afonso, Luis Carlos; Kohlhoff, Markus; Zani, Carlos Leomar; Gazzinelli, Ricardo Tostes; Oliveira, Fabiano; et al. (Frontiers in Immunology, 2023)
Background: Plasmodium spp. infection triggers the production of inflammatory cytokines that are essential for parasite control, and conversely responsible for symptoms of malaria. Monocytes play a role in host defense against Plasmodium vivax infection and represent the main source of inflammatory cytokines and reactive oxygen species. The anti-inflammatory cytokine IL-10 is a key regulator preventing exacerbated inflammatory responses. Studies suggested that different clinical presentations of malaria are strongly associated with an imbalance in the production of inflammatory and anti-inflammatory cytokines. Methods: A convenience sampling of peripheral blood mononuclear cells from Plasmodium vivax-infected patients and healthy donors were tested for the characterization of cytokine and adenosine production and the expression of ectonucleotidases and purinergic receptors. Results: Here we show that despite a strong inflammatory response, monocytes also bear a modulatory role during malaria. High levels of IL-10 are produced during P. vivax infection and its production can be triggered in monocytes by P. vivax-infected reticulocytes. Monocytes express high levels of ectonucleotidases, indicating their important role in extracellular ATP modulation and consequently in adenosine production. Plasmatic levels of adenosine are not altered in patients experiencing acute malaria; however, their monocyte subsets displayed an increased expression of P1 purinergic receptors. In addition, adenosine decreases Tumor Necrosis Factor production by monocytes, which was partially abolished with the blockage of the A2a receptor. Conclusion: Monocytes have a dual role, attempting to control both the P. vivax infection and the inflammatory response. Purinergic receptor modulators emerge as an untapped approach to ameliorate clinical malaria.